Simulation of diffusion processes during electrothermal treatment of reaction crucibles of the Fe-Sn system - Fomin, V.E.; Tukmakova, A.S.; Bolkunov, G.A.; Novotelnova, A.V.; Bochkanov, F.Yu; Karpenkov, D.Yu (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2024)
The diffusion processes regularity in the reaction crucibles of the iron-tin system during their electrothermal treatment was studied by the numerical simulation methods. The effect of current density and temperature on the processes of heat and mass transfer in the reaction zone has been studied. Numerical simulation was performed by the finite element method. The developed model includes mechanical, thermal, electrical and chemical processes during the electrothermal treatment of the iron-tin system in the reaction crucible, taking into account the distribution of components under various processing conditions of the reaction crucible. A comparative analysis of the calculated data on the diffusion of tin into iron under conditions of long-term exposure to high temperatures without the application of an electric voltage and when the reaction zone is heated by passing a high-density electric current is performed. A picture of the distribution of mass fractions of components depending on the type of impact is obtained. The penetration depth of the interacting components was determined and the intensity of the mass transfer processes was assessed. The regularities of heat and mass transfer in the system of iron and tin with a change of the process initial parameters are established. The model was verified by comparing the simulation results with the data of full-scale experiments on control samples. The research results can be used to predict the conditions for obtaining new functional materials.